PENERAPAN MODEL ARIAS SETTING KOOPERATIF JIGSAW DENGAN MEDIA AUDIO VISUAL DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS IV SD - Rizki, Sofiyana (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Implementation of ARIAS Model of Cooperative Jigsaw Setting Through Audio Visual Media In Improving Social Science Learning at The Fourth Grade Students. The objectives of this research are: (1) to describe the implementation of ARIAS model of cooperative jigsaw settings through audio-visual media (2) to describe the improvement of social science learning (3) to identify problems and solutions in the implementation of ARIAS model of cooperative jigsaw settings through audio-visual media. This research is Collaborative Classroom Action Research (CAR) conducted in three cycles. The result show that: (1) the implementation of ARIAS model of cooperative jigsaw settings through audio-visual media was carried out through five stages, namely (a) assurance stage, (b) relevance stage, (c) interest stage; application of cooperative jigsaw settings through audio-visual media, (d) assessment stage, and (e) satisfaction stage, (2) the application of ARIAS model setting cooperative jigsaw with audio visual media can improve Social Science learning (3) Problem occurred in the application of this model was classroom teachers implementing treatment did not understand the steps of model. The solution is that researchers carry out simulation model application and reflection on learning. Keywords: ARIAS, jigsaw, audio visual, learning, Social science Abstrak: Penerapan Model ARIAS Setting Kooperatif Jigsaw dengan Media Audio Visual dalam Peningkatan Pembelajaran IPS Siswa Kelas IV SD. Penelitian ini bertujuan: (1) mendeskripsikan penerapan model ARIAS setting kooperatif jigsaw dengan media audio visual (2) mendiskripsikan peningkatan pembelajaran IPS (3) mengidentifikasi kendala dan solusinya. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaboratif dilaksanakan dalam tiga siklus. Hasil penelitian menunjukkan: (1) penerapan ARIAS setting kooperatif jigsaw dengan media audio visual dilaksanakan melalui lima tahap, yaitu: (a) assurance; (b) relevance; (c) interest; (d) assessment; dan (e) satisfaction dan (2) penerapan model ARIAS setting kooperatif jigsaw dengan media audio visual dapat meningkatkan pembelajaran IPS. (3) kendalanya guru kurang memahami langkah penerapan model, hal ini dapat diatasi dengan simulasi dan refleksi. Kata kunci: ARIAS, kooperatif jigsaw, media audio visual, pembelajaran, IPS.